Cognition and Implementation of Disaster Preparedness among Japanese Dialysis Facilities - Hidehiro Sugisawa; Toshio Shinoda; Yumiko Shimizu; Tamaki Kumagai (International Journal of Nephrology)
Introduction. Few quantitative studies have explored disaster preparedness in dialysis facilities worldwide. This study examined the levels of disaster preparedness and their related factors in dialysis facilities in Japan. Methods. We conducted a mail survey using a self-administered questionnaire for key persons responsible for disaster preparedness in dialysis facilities (N = 904) associated with the Japanese Association of Dialysis Physicians. Levels of disaster preparedness were evaluated by the implementation rates of four domains: (1) patient, (2) administration, (3) network, and (4) safety. Additionally, we focused on cognitive factors related to disaster preparedness, such as risk perception, outcome expectancy, self-efficacy, self-responsibility, and support from the surroundings. Results. A total of 517 participants answered the survey (response rate: 57.2%). Implementation rates differed according to the domains of disaster preparedness. While the average implementation rate of the safety domain was 81.8%, each average implementation rate was 57.9%, 48.3%, and 38.4% for the administration, network, and patient domains, respectively. The study found that self-efficacy and support from the surroundings of the participants were significantly associated with the four domains of disaster preparedness. Alternatively, risk perception and support from surroundings were significantly associated with one particular domain each. Conclusion. Our results suggest that boosting self-efficacy and support from surroundings among key persons of disaster preparedness in dialysis facilities may contribute to the advancement of the different domains of disaster preparedness.